Preparation of CuO/MgO Composite for Removal of Tartrazine in Aqueous Solution - Phan, Thi Yen; Vu, Anh Tuan (Old Journal, 2018)
In this study, the CuO/MgO composite was prepared by co-precipitation method, as-prepared samples were characterized by SEM, TEM, XRD and N₂ adsorption/desorption isotherms. The removal of tartrazine from aqueous solution by CuO/MgO/H₂O₂/UV was investigated and compared to other systems with/without H₂O₂ and UV irradiation. The amount of dye removed was determined by measuring the concentration of the dye at its characteristic wavelengths by UV-Vis spectrophotometer. The removal efficiency observed was in the order: CuO/MgO/UV/H₂O₂>CuO/MgO/H₂O₂>CuO/MgO/UV>CuO/MgO>UV/H₂O₂>UV>H₂O₂. In addition, the pseudo-first order kinetic model was used for fitting the experimental data profiles in order to find the reaction rate constant.